2017
DOI: 10.17576/jsm-2017-4601-06
|View full text |Cite
|
Sign up to set email alerts
|

Biodegration of Tapis Crude Oil Using Consortium of Bacteria and Fungi: Optimization of Crude Oil Concentration and Duration of Incubation by Response Surface Methodology

Abstract: Response surface analysis was conducted to optimize the concentrations of Tapis crude oil and duration of incubation in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…There were significant differences ( p < .01) in the degradation percentage between the fungus in this experiment and that in the previous experiment without biostimulation. It appeared that the longer incubation time presented more efficient results; that is, a higher fungal biomass in contact with the PAH compounds leads to higher levels of PAH degradation (Hamzah, Manikan, & Abd Aziz, 2017; Satti, Shah, Marsh, & Auras, 2018). Several reports state that the degradation process was maximized once optimal conditions for growth were achieved (Ali et al, 2012; Govarthanan et al, 2017; Hamzah et al, 2012; Wu et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…There were significant differences ( p < .01) in the degradation percentage between the fungus in this experiment and that in the previous experiment without biostimulation. It appeared that the longer incubation time presented more efficient results; that is, a higher fungal biomass in contact with the PAH compounds leads to higher levels of PAH degradation (Hamzah, Manikan, & Abd Aziz, 2017; Satti, Shah, Marsh, & Auras, 2018). Several reports state that the degradation process was maximized once optimal conditions for growth were achieved (Ali et al, 2012; Govarthanan et al, 2017; Hamzah et al, 2012; Wu et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…After incubation, we proceeded to review the macroscopic modifications on the films, observing for changes in color, occurrence of holes and development of microorganisms on the surface (Lucas et al, 2008). In addition, the fungus mass was collected, filtered, dried at 60 °C for 72 hours and weighed to compare its growth vs. controls (Hamzah, Manikan, & Abd Aziz, 2017). Also, the spectra of the films were obtained by FTIR at the end of the test and compared with the spectra at the beginning.…”
Section: Screening Of Pvc Degrading Fungimentioning
confidence: 99%
“…is is for the reason that a single bacterial isolate (monoculture) can only utilize a limited range of hydrocarbon substrates [64], while mixed bacterial isolates (polyculture and consortium) are efficient to metabolize highly concentrated and broad hydrocarbon contaminants [30]. is is because consortia of bacteria possess broad degradative enzymes, degrade different hydrocarbon components (aliphatic and aromatics), have a higher tolerance to physic-chemical parameters (temperature, pH, and salinity) and a higher rate of surface-active biomolecules (biosurfactants) synthesis, and cope up with synergistic effect to maximize the rate of bioremediation [65,66]. erefore, understanding community structure, diversity, and interaction is essential to define the metabolic potential (metabolic diversity) and hydrocarbon specificity of hydrocarbon-degrading communities [48].…”
Section: Bacterial Community Structure and Diversity/microbialmentioning
confidence: 99%
“…Hence, the activities of these antagonistic bacteria have to be controlled to encourage the continued development of viable potential bacterial consortia. Many studies showed that microbial communities (bacteria, fungi, yeasts, and algae) play a great role in the biodegradation of hydrocarbon pollutants [56,65]. ere are several bacterial genera that are tested for the degradation of hydrocarbon (Table 2).…”
Section: Bacterial Community Structure and Diversity/microbialmentioning
confidence: 99%